Increased spontaneous CCL2 (MCP‐1) and CCL5 (RANTES) secretion in vitro in LADA compared to type 1 diabetes and type 2 diabetes: Action LADA 14. Issue 7 (16th January 2021) - Ooms, Mark; Strom, Alexander; Strassburger, Klaus; Menart, Barbara; Leslie, Richard D.; Schloot, Nanette C.
Abstract: Aims: Immune‐mediated type 1 diabetes (T1D) in adulthood and latent autoimmune diabetes in adults (LADA) share similar pathological mechanisms but differ clinically in disease progression. The aim of this study was to acquire insights into spontaneous and stimulated chemokine secretion of immune cells in different diabetes types. Materials and Methods: We investigated in vitro spontaneous, mitogen (PI) and antigen (HSP60, p277, pGAD, pIA2) stimulated chemokine secretion of leucocytes from patients with T1D ( n = 32), LADA ( n = 22), type 2 diabetes (T2D; n = 49), and glucose‐tolerant individuals ( n = 13). Chemokine concentration in supernatants was measured for CCL2 (MCP‐1), CXCL10 (IP10) and CCL5 (RANTES) using a multiplex bead array assay. Results: Spontaneous secretion of CCL2 and CCL5 were higher in LADA compared to T1D and T2D (all p < 0.05) while CXCL10 was similar in the groups. Mitogen‐stimulated secretion of CCL2 in LADA was lower compared to T1D and T2D (all p < 0.05) while CXCL10 and CCL5 were similar in all groups. Upon stimulation with pIA2 the secretion of CCL2 in LADA was lower compared to T2D ( p < 0.05). Spontaneous CXCL10 secretion in LADA was positively associated with body mass index ( r 2 = 0.35; p = 0.0035) and C‐peptide ( r 2 = 0.30; p = 0.009). Conclusions: Chemokine secretion is altered between different diabetes types. Increased spontaneous secretion of CCL2 and CCL5 and decreased secretion of CCL2, upon stimulation with PI and pIA2, in LADA compared to T1D and T2D could reflect altered immune responsiveness in LADA patients in association with their slower clinical progression compared to insulin dependence.